A dangerous surgical masquerade - medial arcuate ligament syndrome as acute coronary syndrome: a case report - Subramanian, Preethi; Vaithianathan, Rajan (International Surgery Journal, 2020)
Median arcuate ligament syndrome is an uncommon cause for abdominal pain and weight loss, caused by median arcuate ligament compressing the celiac plexus or artery. Median arcuate ligament is the continuation of the posterior diaphragm which passes superior to celiac artery and surrounds the aorta. In this case report, A 67 year old male presented with complaints of sudden onset chest pain and loss of weight for the past 6 months. CECT thorax and abdomen it showed features of focal stenosis of coeliac axis and post stenotic dilation of the coeliac trunk suggesting median arcuate ligament syndrome. Laparoscopic median arcuate ligament release was done to relieve the patient from symptoms. Diagnosis of median arcuate ligament syndrome should be considered in a patient presenting with chest pain and weight loss with normal cardiac status and unexplained etiology.